Tumor resting-state fMRI connectivity to extralesional brain is associated with cognitive performance in glioma patients - Chuh-Hyoun Na; Hans Clusmann; Martin Wiesmann; Kerstin Jütten; Verena Mainz (Brain and Spine)
Introduction: Functional coupling of the tumor to extralesional brain areas and the pretherapeutic cognitive performance status have each independently been identified as prognostically relevant in glioma patients. It is however unclear, whether tumor-connectivity correlates with cognitive performance or the cognitive outcome. Research question: To investigate potential associations between pre- and postoperative resting-state fMRI connectivity (FC) and cognitive functions in glioma patients compared to healthy controls. Material and methods: 18 patients and 18 age-matched, healthy controls underwent resting-state fMRI and neuropsychological testing pre- and 4.5 months (mean) postoperatively. FC of the tumor to extralesional brain (Tu-EL) was determined, as well as FC of extralesional brain (EL) and the contralesional hemisphere (conEL). Groups were compared with regard to behavioral and FC measures. Results: Patients showed deficits in all cognitive domains tested. While postoperative performance tended to be worse, deterioration was not statistically significant between timepoints. EL FC did not differ between groups, but conEL FC (p < .045) was increased in patients as compared to controls. Tu-EL FC was significantly associated with worse attention performance (p < .001), and, by trend (p < .058), with worse attentional outcome in patients. Discussion and conclusion: Intrinsic functional coupling to the rest of the brain was associated with worse cognitive performance and might relate to pathological tumor-neuron interaction on the macroscale, reflecting the invasive nature of diffusely infiltrating glioma. Deepening our understanding of FC measures at the connectomic level in the context of cancer neuroscience may aid in identifying neurophysiological correlates of cognitive impairment and in prognosticating cognitive outcome in glioma patients.